Standardized Hepatitis B Virus RNA Quantification in Untreated and Treated Chronic Patients: a Promising Marker of Infection Follow-Up - Maria Francesca Cortese; Mar Riveiro-Barciela; David Tabernero; Francisco Rodriguez-Algarra; Adriana Palom; Sara Sopena; Ariadna Rando-Segura; Luisa Roade; Alison Kuchta; Roser Ferrer-Costa; Josep Quer; Beatriz Pacin; et al. (Microbiology Spectrum, 2022)
ABSTRACT The measurement and interpretation of HBV DNA and RNA levels in HBV infected patients treated with antiviral therapy supports the objective of HBV disease management. Here, we quantified circulating HBV RNA through a standardized and sensitive assay in follow-up samples from both naive and treated patients as a marker of infection evolution. HBV DNA (HBV DNA for use in Cobas 6800/8800 Automated Roche Molecular Systems), RNA (Roche HBV RNA Investigational Assay for use in the Cobas 6800/8800; Roche), HBeAg and HBsAg (Elycsys HBsAg chemiluminescence immunoassay by Cobas 8000; Roche), and core-related antigen (Lumipulse G chemiluminescence assay; Fujirebio) levels were measured in cohorts of untreated or nucleos(t)ide treated, HBV-infected subjects in an outpatient hospital setting. HBV DNA levels in untreated people were 3.6 log10 higher than corresponding RNA levels and were stable over 5 years of observation. While only five of 52 treated patients had DNA levels below the lower limit of quantification (10 IU/mL) at the end of follow-up, 13 had HBV RNA levels persistently above this limit, including eight with undetectable DNA. In samples with undetectable core-related antigen we observed a median HBsAg titer 2.7-fold higher than in samples with undetectable RNA (adjusted P = 0.012). Detectable HBV RNA with undetectable HBV DNA was a negative predictor of HBsAg decrease to a level ≤100 IU/mL (P = 0.03). In naive patients the difference between HBV DNA and RNA was higher than previously reported. HBV RNA rapidly decreased during treatment. However, in some cases, it was detectable even after years of effective therapy, being a negative predictor of HBsAg decrease. The investigational RNA assay for use on the Cobas 6800/8800 instruments is a sensitive and standardized method that could be applied in general management of HBV infection. IMPORTANCE This study focused on the quantification of circulating HBV RNA by using a standardized and sensitive assay. Thanks to this system we observed a higher difference between circulating HBV DNA and RNA than previously reported. In treated patients, HBV RNA decreased together with DNA, although some patients presented detectable levels even after years of successful antiviral treatment, suggesting a persistent viral transcription. Of note, the detection of viral RNA when HBV DNA is undetectable was a negative predictor of HBsAg decrease to a level ≤100 IU/mL. This assay could be extremely helpful in HBV patients management to study viral transcription and to identify those treated patients that may achieve sustained viral suppression.